AWARENESS OF LUDWIG’S ANGINA AMONG DENTAL PRACTITIONERS - Thirunavakarasu, Reshma; Ganapathy, Dhanraj; Rohinikumar, Subhashree (International Journal of Psychosocial Rehabilitation, 2019)
Ludwigs angina is a life-threatening cellulitis. It is primarily seen involving the submandibular space followed by secondary involvement of the submental space. This disease has an aggressive characteristic and spreads rapidly causing a compromised airway with little warning.The aim of the study is to determine the level of knowledge and awareness of dental practitioners regarding ludwig’s angina and its management techniques.A total of 10 multiple choice questions were formed and distributed to 100 dental practitoners with more than 5 years of experience. All 10 questions assessed the knowledge of dental practitioners regarding the Ludwig’s angina and awareness of the various management techniques.After all the participants have given their response, their responses were noted and tabulated. All the respondents were aware of cause and causative factors of ludwigs angina.78% said it is a cellulitis.Broad spectrum antibiotics are the choice in 78% of th respondents.80% are aware this condition involve multiple space infections and 64%said they can diagnose this condition based on clinical features.The awareness of managenent techniques of ludwigs angina among were high among the dental practitioners. The importance regarding knowledge of various disease which mainly affects the head and neck region is crucial for dental practitioners. Thus it is essential for the dental practitioners to have knowledge of the conditions and be aware of the managements of these conditions